Impact-resistant modified polyvinyl chloride composite material for pipelines and preparation method of impact-resistant modified polyvinyl chloride composite material

By introducing long-chain groups and nano-calcium carbonate particles into the polyvinyl chloride composite, the problem that existing materials cannot resist combustion during flame combustion is solved, and the material's better impact resistance and flame retardant properties are achieved.

CN119613893AInactive Publication Date: 2025-03-14ANHUI OUPO PIPE TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510152235.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyvinyl chloride composites cannot resist combustion when the flame is burned, and cannot prevent or mitigate damage caused by fire.

Method used

Impact-resistant modified polyvinyl chloride composite materials are used to use pipes including PVC resin, modified impact resistance agent, titanium dioxide, polyethylene wax, organotin stabilizer, calcium stearate and modified nano-calcium carbonate, and the impact resistance and flame retardant properties of the material are improved by combining long-chain groups and nano-calcium carbonate particles.

Benefits of technology

The material has good impact resistance and flame retardant properties, can show high impact resistance when impacted, and effectively retardant when flame burns, reducing fire damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613893A_ABST
    Figure CN119613893A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyvinyl chloride, and discloses an impact-resistant modified polyvinyl chloride composite material for pipelines and a preparation method thereof.Cyanuric chloride, 1-(4-vinyl-2-hydroxyphenyl)-ethanone, vinyltrimethylsilane and 1-thiophospha-4-hydroxymethyl-2, 6, 7-trioxabicyclo [2, 2, 2] octane (SPEPA) are used as raw materials, and the impact-resistant modified polyvinyl chloride composite material for the pipelines is prepared through the steps that the raw materials are subjected to heat preservation at room temperature; the preparation method comprises the following steps: carrying out a substitution reaction and an addition reaction to prepare flame-retardant modified cyanuric chloride silane triene, adding butadiene and methyl methacrylate as raw materials, carrying out a polymerization reaction to prepare a modified impact resistant agent, carrying out a coupling grafting reaction on cyanuric chloride silane triene and nano calcium carbonate as raw materials to prepare modified nano calcium carbonate, and carrying out a polymerization reaction on the modified nano calcium carbonate and the modified nano calcium carbonate to prepare the flame-retardant modified cyanuric chloride silane triene. And finally, by taking the modified impact-resistant agent, PVC resin, modified nano calcium carbonate and the like as raw materials, the prepared impact-resistant modified polyvinyl chloride composite material for the pipeline has relatively good flame retardance and impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl chloride, in particular to an impact-resistant modified polyvinyl chloride composite material for pipelines and a preparation method thereof. Background Art

[0002] Polyvinyl chloride (PVC) is one of the earliest developed plastics and one of the five general-purpose plastics. It has excellent mechanical, insulating, non-flammable, corrosion-resistant and wear-resistant properties, and is inexpensive and has a wide range of raw material sources. It is widely used in plastic pipes, plates, rods, plastic doors and windows, insulation materials, wood-like plastics, films, artificial leather, wires and cables, and packaging materials.

[0003] At present, PVC can be divided into soft PVC and hard PVC. Soft PVC is generally used for floors, ceilings and the surface of leather. Soft PVC contains softener, which makes it easy to become brittle and difficult to preserve. Hard PVC does not contain softener, so it has good flexibility, is easy to shape, is not easy to be brittle, is non-toxic and pollution-free, and has a long shelf life. Therefore, it has great development and application value.

[0004] For example, the patent with authorization announcement number CN116253961B discloses a polyvinyl chloride composite material, a preparation method and an application thereof. The polyvinyl chloride composite material of the invention is prepared by modifying polyvinyl chloride with a heat stabilizer, a plasticizer, a lubricant, a light stabilizer and a nano-inorganic additive, wherein the nano-inorganic additive includes calcium carbonate and talcum powder, and the heat stabilizer is stearate; at the same time, within the above-mentioned mass fraction range, the toughness and impact strength of the polyvinyl chloride composite material are improved, but the composite material prepared by this invention cannot resist combustion when subjected to flame combustion, thereby preventing the occurrence of fire or reducing the damage caused by fire. Summary of the invention

[0005] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides an impact-resistant modified polyvinyl chloride composite material for pipes and a preparation method thereof. The prepared impact-resistant modified polyvinyl chloride composite material has good impact resistance and flame retardancy. Technical Solution

[0006] An impact-resistant modified polyvinyl chloride composite material for pipes comprises the following components in parts by weight: 100 parts by weight of PVC resin, 5-12 parts by weight of a modified impact-resistant agent, 1-3 parts by weight of titanium dioxide, 0.1-0.3 parts by weight of polyethylene wax, 0.2-0.8 parts by weight of an organic tin stabilizer, 0.2-0.8 parts by weight of calcium stearate and 8-12 parts by weight of modified nano calcium carbonate.

[0007] Preferably, the preparation method of the impact-resistant modified polyvinyl chloride composite material is as follows: (1) Emulsifier octylphenol polyoxyethylene ether (OP-10), potassium hydroxide, Rongalite, reducing agent ferrous sulfate, sodium phosphate, initiator potassium persulfate are sequentially added into a high-pressure reactor, replaced with nitrogen, flame-retardant modified tripolychlorocyanosilane triene is added, stirred and mixed evenly, heated to 60-80°C, butadiene is added, reacted for 10-14h, butadiene is stopped, heat is maintained for 5-7h, cooled to room temperature, agglomerating agent carbon dioxide is introduced, pH is adjusted to 7-8, filtered, and the product is added to a flask. Add deionized water, ferrous sulfate, and persulfate, stir, pass nitrogen to drive oxygen, add 5% potassium hydroxide and methyl methacrylate (MMA) washed with deionized water, heat to 60-80°C, react for 3-5h, cool after the reaction, filter, dilute with deionized water, stir and mix, heat to 50-70°C, add flocculant sulfur dioxide, react for 3-5min, heat to 75-95°C, mature for 1-3h, filter, wash, and dry to obtain a modified impact resistance agent; (2) Add polyvinyl chloride resin and organic tin stabilizer into a high-speed mixer, stir and mix for 3-7 minutes, heat to 70-80°C, add polyethylene wax and calcium stearate, mix evenly, heat to 85-95°C, finally add modified nano calcium carbonate, titanium dioxide, and modified impact resistance agent, heat to 100-110°C, stop the machine to discharge, cool the cold mixer, vacuum suck out, and sieve with a vibrating screen to obtain an impact-resistant modified polyvinyl chloride composite material for pipelines.

[0008] Preferably, in step (1), the mass ratio of emulsifier OP-10, potassium hydroxide, Rongbai, ferrous sulfate, sodium phosphate, persulfate, flame retardant modified tripolychlorocyanosilanetriene, butadiene, MMA, and sulfur dioxide is 1:0.08-0.09:0.25-0.35:0.000055-0.000065:0.008-0.009:0.02-0.03:32-36:1-1.2:0.75-0.85:0.0002-0.0036.

[0009] Preferably, the preparation method of the flame retardant modified tricyandiamide silanetriene is: (1) Under a nitrogen atmosphere, 4-vinylbenzoic acid, polymerization inhibitor p-hydroxyanisole (MEHQ), and catalyst tetrabutylammonium bromide (TBAB) are added to a methanol solvent, and γ-glycidyloxypropyltrimethoxysilane is added, and the temperature is raised to 70-90°C, and the reaction is carried out for 8-12 hours. After the reaction is completed, the temperature is lowered to room temperature, filtered, washed, and dried to obtain intermediate 1; (2) Add cyanuric chloride, intermediate 1 and sodium hydroxide into acetone solvent, stir and mix evenly, react for 60-90 minutes, cool, distill under reduced pressure, drain, and recrystallize from petroleum ether to obtain cyanuric chloride silanetriene; (3) Under nitrogen atmosphere, add trichlorocyanosilanetriene to 1-thiophospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2,2,2]octane (SPEPA), heat to 90-110°C, fractionate and react for 1-3h, then heat to 130-150°C, fractionate and react for 4-6h, remove methanol, cool to 35-45°C, disperse with anhydrous ethanol, filter and dry to obtain flame retardant modified trichlorocyanosilanetriene.

[0010] Preferably, in step (1), the molar ratio of 4-vinylbenzoic acid, MEHQ, TBAB and γ-glycidyloxypropyltrimethoxysilane is 1:0.004-0.006:0.002-0.004:0.015-0.025.

[0011] Preferably, in step (2), the molar ratio of cyanuric chloride, intermediate 1, and sodium hydroxide is 1:0.4-0.6:0.5-0.7.

[0012] Preferably, in step (3), the molar ratio of trichlorocyanosilanetriene to SPEPA is 1:5.5-6.5.

[0013] Preferably, the preparation method of the modified nano calcium carbonate is: Add nano calcium carbonate powder into anhydrous ethanol, ultrasonically disperse for 30-90 minutes, heat to 70-90°C, add tripolychlorocyanosilanetriene, reflux for 30-90 minutes, filter, extract with acetone, and dry to obtain modified nano calcium carbonate.

[0014] Preferably, the molar ratio of nano calcium carbonate powder to trichlorocyanosilanetriene is 1:0.05-0.15.

[0015] 3. Beneficial technical effects The invention uses cyanuric chloride, 1-(4-vinyl-2-hydroxyphenyl)-ethanone, vinyl trimethylsilane and 1-sulfaphospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2,2,2]octane (SPEPA) as raw materials, and obtains flame retardant modified cyanuric chloride silane triene through substitution reaction and addition reaction. Then, butadiene and methyl methacrylate are added as raw materials, and a modified impact resistant agent is obtained through polymerization reaction. Using cyanuric chloride silane triene and nano calcium carbonate powder as raw materials, a coupling grafting reaction is performed to obtain modified nano calcium carbonate. Finally, using the modified impact resistant agent, PVC resin, modified nano calcium carbonate and the like as raw materials, an impact resistant modified polyvinyl chloride composite material for pipelines is obtained.

[0016] The impact-resistant modified polyvinyl chloride composite material for pipes prepared by the present invention has long-chain groups that can effectively absorb and disperse externally applied stress and reduce brittleness. At the same time, van der Waals forces are formed between the long chains, which can improve the strength of the PVC pipe. Therefore, the introduction of the long-chain groups can effectively improve the flexibility of the PVC pipe. At the same time, the nano calcium carbonate particles play a role in dividing the matrix in the resin. This division naturally causes the material to form defects similar to microcracks. When the PVC pipe is subjected to an impact load, these microcracks will expand, resulting in a decrease in impact strength and improved impact resistance. Therefore, the PVC pipe has a certain impact resistance.

[0017] The impact-resistant modified polyvinyl chloride composite material for pipes prepared by the present invention contains phosphorus, nitrogen and silicon elements, wherein the triazine group containing nitrogen element will decompose to produce a large amount of non-combustible gas during combustion, and the non-combustible gas can dilute the oxygen concentration around the composite material, and the silicon element can migrate to the outside of the material during combustion, and the Si-O bond in its molecule will be converted into Si-C bond, and the generated white combustion residue and carbide will form a covering layer on the surface of the composite material, preventing the combustion volatiles from escaping and preventing oxygen from contacting the matrix material, thereby improving the flame retardant performance of the pipe, and the phosphorus element will release a large amount of gas or high-density steam when heated or burned, which can dilute the oxygen and gaseous combustibles in the air, and reduce the surface temperature of the combustion object, so as to stop the combustion. The impact-resistant modified polyvinyl chloride composite material for pipes prepared by the present invention has good flame retardant performance and impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a preparation route for flame retardant modified tricyandiamide silane triene. DETAILED DESCRIPTION

[0019] The present invention will be further explained below in conjunction with specific embodiments. Embodiment 1

[0020] (1) Under nitrogen atmosphere, 0.1 mol of 4-vinylbenzoic acid, 0.6 mmol of polymerization inhibitor p-hydroxyanisole (MEHQ), and 0.2 mmol of catalyst tetrabutylammonium bromide (TBAB) were added to 50 ml of methanol solvent, and 20 mmol of γ-glycidyloxypropyltrimethoxysilane was added, and the temperature was raised to 60°C. The reaction was allowed to proceed for 8 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed, and dried to obtain intermediate 1; (2) Add 0.1 mol of cyanuric chloride, 0.06 mol of intermediate 1, and 0.05 mol of sodium hydroxide into 50 ml of acetone solvent, stir and mix evenly, react for 90 min, cool, distill under reduced pressure, drain, and recrystallize from petroleum ether to obtain cyanuric chloride silanetriene; (3) Under nitrogen atmosphere, 0.1 mol of trichlorocyanosilane triene was added to 0.65 mol of 1-sulfaphospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2,2,2]octane (SPEPA), the temperature was raised to 110°C, the reaction was fractionated for 1 hour, the temperature was raised to 130°C, the reaction was fractionated for 6 hours, methanol was removed, the temperature was lowered to 35°C, anhydrous ethanol was stirred and dispersed, suction filtered, and dried to obtain flame retardant modified trichlorocyanosilane triene; (4) Add 0.1 mol of nano-calcium carbonate powder to 50 ml of anhydrous ethanol, disperse by ultrasonication for 90 min, heat to 70°C, add 15 mmol of tripolychlorocyanosilanetriene, reflux for 30 min, filter, extract with acetone, and dry to obtain modified nano-calcium carbonate; (5) 10 parts by weight of an emulsifier octylphenol polyoxyethylene ether (OP-10), 0.9 parts by weight of potassium hydroxide, 2.5 parts by weight of Rongbai, 0.00055 parts by weight of a reducing agent ferrous sulfate, 0.09 parts by weight of sodium phosphate, and 0.3 parts by weight of an initiator potassium persulfate were sequentially placed in a high-pressure reactor, replaced with nitrogen, 320 parts by weight of flame-retardant modified tripolychlorocyanosilanetriene were added, stirred and mixed evenly, the temperature was raised to 80°C, 10 parts by weight of butadiene were added, the reaction was continued for 14 hours, the introduction of butadiene was stopped, the temperature was kept for 7 hours, the temperature was lowered to room temperature, and the attached The polymerizing agent carbon dioxide is added, the pH is adjusted to 7, filtered, the product is added to a flask, deionized water, ferrous sulfate, and persulfate are added, stirred, nitrogen is passed to drive out oxygen, and then 8.5 parts by weight of methyl methacrylate (MMA) washed with 5% potassium hydroxide and deionized water is added, the temperature is raised to 80°C, and the reaction is carried out for 5 hours. After the reaction is completed, the temperature is lowered, filtered, diluted with deionized water, stirred and mixed, the temperature is raised to 50°C, 0.002 parts by weight of flocculant sulfur dioxide is added, the reaction is carried out for 3 minutes, the temperature is raised to 75°C, ripened for 3 hours, filtered, washed, and dried to obtain a modified impact resistance agent; (6) Add 10 parts by weight of polyvinyl chloride resin and 0.02 parts by weight of organic tin stabilizer into a high-speed mixer, stir and mix for 7 minutes, heat to 70°C, add 0.015 parts by weight of polyethylene wax and 0.02 parts by weight of calcium stearate, mix evenly, heat to 85°C, and finally add 0.8 parts by weight of modified nano calcium carbonate, 0.15 parts by weight of titanium dioxide, and 0.5 parts by weight of modified impact-resistant agent, heat to 100°C, stop discharging, cool in a cold mixer, vacuum suck out, and sieve with a vibrating screen to obtain an impact-resistant modified polyvinyl chloride composite material for pipelines. Embodiment 2

[0021] (1) Under nitrogen atmosphere, 0.1 mol of 4-vinylbenzoic acid, 0.4 mmol of polymerization inhibitor MEHQ, and 0.4 mmol of TBAB were added to 50 ml of methanol solvent, and 15 mmol of γ-glycidyloxypropyltrimethoxysilane was added. The temperature was raised to 70°C and the reaction was carried out for 12 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed, and dried to obtain intermediate 1; (2) Add 0.1 mol of cyanuric chloride, 0.04 mol of intermediate 1, and 0.07 mol of sodium hydroxide into 50 ml of acetone solvent, stir and mix evenly, react for 60 min, cool, distill under reduced pressure, drain, and recrystallize from petroleum ether to obtain cyanuric chloride silanetriene; (3) Under nitrogen atmosphere, 0.1 mol of tripolychlorocyanosilanetriene was added to 0.55 mol of SPEPA, the temperature was raised to 90°C, and the reaction was fractionated for 3 hours, and then the temperature was raised to 150°C, and the reaction was fractionated for 4 hours, methanol was removed, the temperature was lowered to 45°C, anhydrous ethanol was stirred and dispersed, filtered, and dried to obtain flame retardant modified tripolychlorocyanosilanetriene; (4) Add 0.1 mol of nano-calcium carbonate powder to 50 ml of anhydrous ethanol, perform ultrasonic dispersion for 60 min, heat to 90°C, add 5 mmol of tripolychlorocyanosilanetriene, reflux for 60 min, filter, extract with acetone, and dry to obtain modified nano-calcium carbonate; (5) 10 parts by weight of emulsifier OP-10, 0.8 parts by weight of potassium hydroxide, 3.5 parts by weight of Rongalite, 0.00065 parts by weight of reducing agent ferrous sulfate, 0.08 parts by weight of sodium phosphate, and 0.2 parts by weight of initiator potassium persulfate were sequentially placed in a high-pressure reactor, replaced with nitrogen, 360 parts by weight of flame-retardant modified tripolychlorocyanosilanetriene were added, stirred and mixed evenly, heated to 60°C, 12 parts by weight of butadiene were added, reacted for 10 hours, butadiene was stopped, the temperature was kept for 5 hours, cooled to room temperature, and the attached The polymerizing agent carbon dioxide is added, the pH is adjusted to 8, filtered, the product is added to a flask, and then deionized water, ferrous sulfate, and persulfate are added, stirred, nitrogen is passed to drive out oxygen, and then 7.5 parts by weight of MMA washed with 5% potassium hydroxide and deionized water are added, the temperature is raised to 60°C, and the reaction is carried out for 3 hours. After the reaction is completed, the temperature is lowered, filtered, diluted with deionized water, stirred and mixed, the temperature is raised to 50°C, 0.036 parts by weight of flocculant sulfur dioxide is added, the reaction is carried out for 3 minutes, the temperature is raised to 75°C, and the temperature is aged for 3 hours, filtered, washed, and dried to obtain a modified impact resistance agent; (6) Add 10 parts by weight of polyvinyl chloride resin and 0.08 parts by weight of organic tin stabilizer into a high-speed mixer, stir and mix for 3 minutes, heat to 75°C, add 0.2 parts by weight of polyethylene wax and 0.06 parts by weight of calcium stearate, mix evenly, heat to 95°C, and finally add 1.2 parts by weight of modified nano calcium carbonate, 0.3 parts by weight of titanium dioxide, and 1.2 parts by weight of modified impact-resistant agent, heat to 110°C, stop discharging, cool with a cold mixer, vacuum suck out, and sieve with a vibrating screen to obtain an impact-resistant modified polyvinyl chloride composite material for pipelines. Embodiment 3

[0022] (1) Under nitrogen atmosphere, 0.1 mol of 4-vinylbenzoic acid, 0.5 mmol of polymerization inhibitor MEHQ, and 0.3 mmol of TABA were added to 50 ml of methanol solvent, and 25 mmol of γ-glycidyloxypropyltrimethoxysilane was added. The temperature was raised to 65°C and the reaction was carried out for 10 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed, and dried to obtain intermediate 1; (2) Add 0.1 mol of cyanuric chloride, 0.05 mol of intermediate 1, and 0.06 mol of sodium hydroxide into 50 ml of acetone solvent, stir and mix evenly, react for 80 min, cool, distill under reduced pressure, drain, and recrystallize from petroleum ether to obtain cyanuric chloride silanetriene; (3) Under nitrogen atmosphere, 0.1 mol of trichlorocyanosilanetriene was added to 0.60 mol of SPEPA, the temperature was raised to 100°C, and the reaction was fractionated for 2 hours, and then the temperature was raised to 140°C, and the reaction was fractionated for 5 hours, methanol was removed, the temperature was lowered to 40°C, anhydrous ethanol was stirred and dispersed, filtered, and dried to obtain flame retardant modified trichlorocyanosilanetriene; (4) Add 0.1 mol of nano-calcium carbonate powder to 50 ml of anhydrous ethanol, perform ultrasonic dispersion for 80 min, heat to 80°C, add 15 mmol of tripolychlorocyanosilanetriene, reflux for 50 min, filter, extract with acetone, and dry to obtain modified nano-calcium carbonate; (5) 10 parts by weight of emulsifier OP-10, 0.85 parts by weight of potassium hydroxide, 3 parts by weight of Rongalite, 0.00065 parts by weight of reducing agent ferrous sulfate, 0.085 parts by weight of sodium phosphate, and 0.25 parts by weight of initiator potassium persulfate were sequentially placed in a high-pressure reactor, replaced with nitrogen, 340 parts by weight of flame-retardant modified tripolychlorocyanosilanetriene were added, stirred and mixed evenly, heated to 80°C, 11 parts by weight of butadiene were added, reacted for 12 hours, the introduction of butadiene was stopped, the temperature was kept for 6 hours, the temperature was lowered to room temperature, and the reaction mixture was heated to 80°C. Add carbon dioxide as a coagulation agent, adjust the pH to 7, filter, add the product to a flask, add deionized water, ferrous sulfate, and persulfate, stir, pass nitrogen to drive out oxygen, add 8 parts by weight of MMA washed with 5% potassium hydroxide and deionized water, heat to 80°C, react for 5 hours, cool, filter, dilute with deionized water, stir and mix, heat to 50°C, add 0.03 parts by weight of flocculant sulfur dioxide, react for 3 minutes, heat to 75°C, mature for 3 hours, filter, wash, and dry to obtain a modified impact resistance agent; (6) Add 10 parts by weight of polyvinyl chloride resin and 0.08 parts by weight of organic tin stabilizer into a high-speed mixer, stir and mix for 7 minutes, heat to 80°C, add 0.03 parts by weight of polyethylene wax and 0.08 parts by weight of calcium stearate, mix evenly, heat to 90°C, and finally add 1 part by weight of modified nano calcium carbonate, 0.2 parts by weight of titanium dioxide, and 1 part by weight of modified impact-resistant agent, heat to 105°C, stop discharging, cool with a cold mixer, vacuum suck out, and sieve with a vibrating screen to obtain an impact-resistant modified polyvinyl chloride composite material for pipelines. Embodiment 4

[0023] (1) Under nitrogen atmosphere, 0.1 mol of 4-vinylbenzoic acid, 0.6 mmol of polymerization inhibitor MEHQ, and 0.2 mmol of TBAB were added to 50 ml of methanol solvent, and 20 mmol of γ-glycidyloxypropyltrimethoxysilane was added. The temperature was raised to 60°C and the reaction was carried out for 8 h. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed, and dried to obtain intermediate 1; (2) Add 0.1 mol of cyanuric chloride, 0.06 mol of intermediate 1, and 0.05 mol of sodium hydroxide into 50 ml of acetone solvent, stir and mix evenly, react for 90 min, cool, distill under reduced pressure, drain, and recrystallize from petroleum ether to obtain cyanuric chloride silanetriene; (3) Under nitrogen atmosphere, 0.1 mol of trichlorocyanosilane triene was added to 0.65 mol of 1-sulfaphospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2,2,2]octane (SPEPA), the temperature was raised to 110°C, the reaction was fractionated for 1 hour, the temperature was raised to 130°C, the reaction was fractionated for 6 hours, methanol was removed, the temperature was lowered to 35°C, anhydrous ethanol was stirred and dispersed, suction filtered, and dried to obtain flame retardant modified trichlorocyanosilane triene; (4) Add 0.1 mol of nano-calcium carbonate powder to 50 ml of anhydrous ethanol, disperse by ultrasonication for 90 min, heat to 70°C, add 15 mmol of tripolychlorocyanosilanetriene, reflux for 30 min, filter, extract with acetone, and dry to obtain modified nano-calcium carbonate; (5) 10 parts by weight of an emulsifier octylphenol polyoxyethylene ether (OP-10), 0.9 parts by weight of potassium hydroxide, 2.5 parts by weight of Rongbai, 0.00055 parts by weight of a reducing agent ferrous sulfate, 0.09 parts by weight of sodium phosphate, and 0.3 parts by weight of an initiator potassium persulfate were sequentially placed in a high-pressure reactor, replaced with nitrogen, 320 parts by weight of flame-retardant modified tripolychlorocyanosilanetriene were added, stirred and mixed evenly, the temperature was raised to 80°C, 10 parts by weight of butadiene were added, the reaction was continued for 14 hours, the introduction of butadiene was stopped, the temperature was kept for 7 hours, the temperature was lowered to room temperature, and the attached The polymerizing agent carbon dioxide is added, the pH is adjusted to 7, filtered, the product is added to a flask, deionized water, ferrous sulfate, and persulfate are added, stirred, nitrogen is passed to drive out oxygen, and then 8.5 parts by weight of methyl methacrylate (MMA) washed with 5% potassium hydroxide and deionized water is added, the temperature is raised to 80°C, and the reaction is carried out for 5 hours. After the reaction is completed, the temperature is lowered, filtered, diluted with deionized water, stirred and mixed, the temperature is raised to 50°C, 0.002 parts by weight of flocculant sulfur dioxide is added, the reaction is carried out for 3 minutes, the temperature is raised to 75°C, ripened for 3 hours, filtered, washed, and dried to obtain a modified impact resistance agent; (6) Add 10 parts by weight of polyvinyl chloride resin and 0.02 parts by weight of organic tin stabilizer into a high-speed mixer, stir and mix for 7 minutes, heat to 70°C, add 0.015 parts by weight of polyethylene wax and 0.02 parts by weight of calcium stearate, mix evenly, heat to 85°C, and finally add 0.96 parts by weight of modified nano calcium carbonate, 0.15 parts by weight of titanium dioxide, and 0.6 parts by weight of modified impact-resistant agent, heat to 100°C, stop discharging, cool in a cold mixer, vacuum suck out, and sieve with a vibrating screen to obtain an impact-resistant modified polyvinyl chloride composite material for pipelines.

[0024] Comparative Example 1 The difference between this comparative example and Example 1 is that the flame retardant modified trichlorocyanuric silanetriene in step (5) is replaced by styrene.

[0025] Impact resistance test Elongation at break According to the GB / T1040-92 method, 5g of Examples 1-4 and Comparative Example 1 were taken respectively, and the elongation at break was calculated at a stretching speed of 10±5min:

[0026] Where ε1 is elongation at break, % G0——initial value of the sample gauge length, mm; G —— gauge length value when the specimen breaks, mm.

[0027] Determination of tensile strength The tensile properties were measured according to the method of GB / T1040-92, taking 5 g of Examples 1-4 and Comparative Example 1, respectively, at a stretching speed of 20±5 mm / min.

[0028] Determination of impact strength The impact toughness of the material is characterized by the work consumed per unit area of ​​the specimen, which is measured using a CEAST6545 impact testing machine. According to the GB / T1043-93 method, impact force is applied to a horizontally placed specimen supported at both ends under the specified standard test conditions to cause the specimen to rupture.

[0029] Table 1: Impact test results of various embodiments and comparative examples <![CDATA[Impact strength (J / m 2 )]]> Tensile strength (MPa) Elongation at break Example 1 165 45.3 105% Example 2 183 46.2 110% Example 3 180 47.0 119% Example 4 176 46.5 114% Comparative Example 1 155 42.5 84% As shown in Table 1, the impact resistance value of Comparative Example 1 is smaller than that of other embodiments, indicating that its flexibility is poor. In contrast, the impact resistance values ​​of Examples 1-4 are all higher than 160 J / m 2 , and no cracks were observed on the coating surface. The reason is that the long-chain groups can effectively absorb and disperse the externally applied stress and reduce brittleness. At the same time, the van der Waals force is formed between the long chains, which can improve the strength of the PVC pipe. Therefore, the introduction of long-chain groups can effectively improve the flexibility of the PVC pipe. At the same time, the nano-calcium carbonate particles play a role in dividing the matrix in the resin. This division naturally causes the material to form defects similar to microcracks. When the PVC pipe is subjected to impact loads, these microcracks will expand, resulting in a decrease in impact strength and improved impact resistance. Therefore, with the increase in the amount of flame-retardant modified tripolychlorocyanosilane triene and modified nano-calcium carbonate, the impact resistance increases, and it has a certain impact resistance.

[0030] Flame retardant performance testing Limiting oxygen index test: The test was performed according to ASTM D 2863-2017. 10 g of the materials of Examples 1-4 and Comparative Example 1 were taken respectively and prepared into a size of 100 mm × 10 mm × 10 mm. The larger the oxygen index (LOI) value, the better the flame retardant performance.

[0031] Table 2: Oxygen index test results of various embodiments and comparative examples Oxygen index (LOI / %) Example 1 32.3 Example 2 37.6 Example 3 35.2 Example 4 33.5 Comparative Example 1 28.3 As can be seen from Table 2, the oxygen index of Comparative Example 1 is smaller than that of other embodiments. The reason is that Examples 1-4 contain phosphorus, nitrogen and silicon elements, among which the triazine group containing nitrogen element will decompose and produce a large amount of non-combustible gas during combustion, and the non-combustible gas can dilute the concentration of oxygen around the composite material. The silicon element can migrate to the outside of the material during combustion, and the Si-O bond in its molecule will be converted into Si-C bond. The generated white combustion residue and carbide form a covering layer on the surface of the composite material, preventing the escape of combustion volatiles and preventing oxygen from contacting the matrix material, thereby improving the flame retardant performance of the pipeline. The phosphorus element will release a large amount of gas or high-density steam when heated or burned, which can dilute the oxygen and gaseous combustibles in the air, and reduce the surface temperature of the combustion object, causing the combustion to stop. The impact-modified polyvinyl chloride composite material for pipelines prepared by the present invention has good flame retardant and impact resistance.

Claims

1. An impact-resistant modified polyvinyl chloride composite material for pipes, characterized in that: The invention comprises the following components in parts by weight: 100 parts by weight of PVC resin, 5-12 parts by weight of modified impact resistance agent, 1-3 parts by weight of titanium dioxide, 0.1-0.3 parts by weight of polyethylene wax, 0.2-0.8 parts by weight of organic tin stabilizer, 0.2-0.8 parts by weight of calcium stearate and 8-12 parts by weight of modified nano calcium carbonate.

2. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 1, characterized in that: The preparation method of the impact-resistant modified polyvinyl chloride composite material is as follows: (1) Emulsifier octylphenol polyoxyethylene ether (OP-10), potassium hydroxide, Rongalite, reducing agent ferrous sulfate, sodium phosphate, initiator potassium persulfate are sequentially added into a high-pressure reactor, replaced with nitrogen, flame-retardant modified tripolychlorocyanosilane triene is added, stirred and mixed evenly, heated to 60-80°C, butadiene is added, reacted for 10-14h, butadiene is stopped, heat is maintained for 5-7h, cooled to room temperature, agglomerating agent carbon dioxide is introduced, pH is adjusted to 7-8, filtered, and the product is added to a flask. Add deionized water, ferrous sulfate, and persulfate, stir, pass nitrogen to drive oxygen, add 5% potassium hydroxide and methyl methacrylate (MMA) washed with deionized water, heat to 60-80°C, react for 3-5h, cool after the reaction, filter, dilute with deionized water, stir and mix, heat to 50-70°C, add flocculant sulfur dioxide, react for 3-5min, heat to 75-95°C, mature for 1-3h, filter, wash, and dry to obtain a modified impact resistance agent; (2) Add polyvinyl chloride resin and organic tin stabilizer into a high-speed mixer, stir and mix for 3-7 minutes, heat to 70-80°C, add polyethylene wax and calcium stearate, mix evenly, heat to 85-95°C, finally add modified nano calcium carbonate, titanium dioxide, and modified impact resistance agent, heat to 100-110°C, stop the machine to discharge, cool the cold mixer, vacuum suck out, and sieve with a vibrating screen to obtain an impact-resistant modified polyvinyl chloride composite material for pipelines.

3. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 2, characterized in that: In the step (1), the mass ratio of emulsifier OP-10, potassium hydroxide, Rongbai, ferrous sulfate, sodium phosphate, persulfate, flame retardant modified tripolychlorocyanosilanetriene, butadiene, MMA, and sulfur dioxide is 1:0.08-0.09:0.25-0.35:0.000055-0.000065:0.008-0.009:0.02-0.03:32-36:1-1.2:0.75-0.85:0.0002-0.0036.

4. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 2, characterized in that: The preparation method of the flame retardant modified tripolychlorocyanosilanetriene: Under nitrogen atmosphere, 4-vinylbenzoic acid, polymerization inhibitor p-hydroxyanisole (MEHQ), catalyst tetrabutylammonium bromide (TBAB) were added to methanol solvent, γ-glycidyloxypropyltrimethoxysilane was added, the temperature was raised to 60-70°C, and the reaction was carried out for 10-14 hours. After the reaction was completed, the temperature was lowered to room temperature, filtered, washed, and dried to obtain intermediate 1; (2) Add cyanuric chloride, intermediate 1 and sodium hydroxide into acetone solvent, stir and mix evenly, react for 60-90 minutes, cool, distill under reduced pressure, drain, and recrystallize from petroleum ether to obtain cyanuric chloride silanetriene; (3) Under nitrogen atmosphere, add trichlorocyanosilanetriene to 1-thiophospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2,2,2]octane (SPEPA), heat to 90-110°C, fractionate and react for 1-3h, then heat to 130-150°C, fractionate and react for 4-6h, remove methanol, cool to 35-45°C, disperse with anhydrous ethanol, filter and dry to obtain flame retardant modified trichlorocyanosilanetriene.

5. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 4, characterized in that: In the step (1), the molar ratio of 4-vinylbenzoic acid, MEHQ, TBAB, and γ-glycidyloxypropyltrimethoxysilane is 1:0.004-0.006:0.002-0.004:0.015-0.

025.

6. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 4, characterized in that: In the step (2), the molar ratio of cyanuric chloride, intermediate 1, and sodium hydroxide is 1:0.4-0.6:0.5-0.

7.

7. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 4, characterized in that: In the step (3), the molar ratio of trichlorocyanosilanetriene to SPEPA is 1:5.5-6.

5.

8. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 2, characterized in that: The preparation method of the modified nano calcium carbonate: Add nano calcium carbonate powder into anhydrous ethanol, ultrasonically disperse for 30-90 minutes, heat to 70-90°C, add tripolychlorocyanosilanetriene, reflux for 30-90 minutes, filter, extract with acetone, and dry to obtain modified nano calcium carbonate.

9. The method for preparing the impact-resistant modified polyvinyl chloride composite material for pipes according to claim 8, characterized in that: The molar ratio of nano calcium carbonate powder to trichlorocyanosilanetriene is 1:0.05-0.15.

Citation Information

Patent Citations

  • A polyvinyl chloride composite material and its preparation method and application

    CN116253961B

  • Isocyanuric acid tris (2-(dimethylthioto-PEPA oxyl silicon acyloxy) ethyl) ester compound and preparation method thereof

    CN104650146A

  • Inorganic nanoparticle modified PVC composite material craft shoe sole and preparation method thereof

    CN111100404A

  • High-impact-resistance polyvinyl chloride drainage pipe and preparation method thereof

    CN111647242A

  • Method for solidifying natural latex by adopting high-pressure carbon dioxide

    CN111718432A